Menggali Moralitas Siswa dalam Kebijakan Non-Expulsion: Implementasi Kurikulum Merdeka di Indonesia - Susanti, Dwi; Airohmah, Yesi; Ikramina, Mahreshaibati Bilqis; Fitriana, Deva Rizkia; Ghufron, David Maulana; Rahman, Abdul (PAKAR Pendidikan, 2025)
This study aims to analyze the impact of the non-expulsion policy on student morality in the context of implementing the Merdeka Curriculum, as well as provide practical recommendations for educators, schools, and policymakers in creating an inclusive learning environment and supporting quality education. This study uses a descriptive qualitative approach with primary data sources obtained from in-depth interviews with five teachers and five students and secondary data from various related literature. Data analysis was conducted through triangulation to ensure the credibility of the results. The results showed that (1) the non-expulsion policy received mixed responses. Some parties considered this policy ineffective because it did not have a deterrent effect on students with serious offences. In contrast, others viewed this policy as in line with the principle of inclusiveness of Merdeka Curriculum, provided it was implemented with the right strategy. Supporting statistical data shows that more than 60% of teachers agree with implementing this policy if accompanied by intensive coaching. (2) The implementation of the Merdeka Curriculum, which integrates religious habituation in schools, has positively impacted student morality, as seen from the increase in discipline, intrinsic awareness of worship, and student's ability to respond ethically to immoral situations. This finding confirms the importance of education that emphasizes moral and religious values in shaping student character and the need to strengthen non-expulsion policies with a sustainable pedagogical approach.